Pengaruh Rasio Aktivitas dan Rasio Leverage Terhadap Financial Distress (Studi Kasus pada Perusahaan Sub Sektor Tekstil dan Garment yang terdaftar di Bursa Efek Indonesia Tahun 2011-2015) - Komala, Adeh Ratna; Novelieta, Candy (Program Studi Akuntansi | Fakultas Ekonomi dan Bisnis | Universitas Komputer Indonesia, 2018)
This research was conducted in companies textile and garment sub sector listed on Indonesian Stock Exchange in the period 2011-2015. The phenomenon that occurs is in some companies textile and garment sub sector has experienced financial distress when the company has a activity ratio and leverage ratio are good. This research was purpose to find out how much influence activity ratio and leverage ratio effect to financial distress. The method used in this research is descriptive method verification with quantitative approach. The sampling method in this study using nonprobability sampling with purposive sampling approach. The unit of analysis in this research is 45 the company's annual financial report taken in 2011 - 2015. The data were analyzed using multiple linear regression. Testing the hypothesis in this study using the statistical t-test statistic with SPSS 16.0 for Windows. Results from this study showed that the activity ratio significantly influence to financial distress in companies textile and garment sub sector listed on Indonesian Stock Exchange. As well as the results of this study also showed that leverage ratio significantly influence financial distress in textile and garment sub sector listed on Indonesian Stock Exchange. Keywords: activity ratio, leverage ratio, financial distress.